PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR HARIAN RADAR MAKASSAR - Saldiaman; Anwar Ramli; Chalid Imran Musa; Muh. Ichwan Musa; Tenri Sayu Puspitaningsih Dipoatmodjo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
This study aims to determine the effect of work motivation and discipline on employee performance at the Daily Radar Makassar Office. The population in this study was the number of samples used as many as 40 people using random sampling theory. Data collection techniques used by using the method of description and distribution of questionnaires. The data analysis technique used is multiple linear analysis using Statistical Product and Service Solution (SPSS). The results of this study indicate that the two independent variables, namely motivation (X1) and work discipline (X2) have a partial relationship or influence and a simultaneous relationship or influence on the dependent variable, namely employee performance (Y).